Volatility transmission among Latin American stock markets under structural breaks - KAYA SOYLU, PINAR (ELSEVIER, 2016)
The paper investigates the volatility spillovers among five major Latin American (LA) stock markets under the presence of the structural breaks in variance. We employ a multivariate dynamic conditional correlation (DCC GARCH) model allowing for structural breaks in variance. The dynamic correlations show that volatility spillover effects among the markets are not strong. Causality in mean tests indicate one way causality from BOVESPA to all markets, whereas causality in variance tests indicate one way causality only from BOVESPA to IPSA. These findings suggest that while the markets in the sample are interdependent, there is not enough statistical evidence to infer the contagion effects among the markets. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Volatility spillovers; Breaks in variance; DCC-GARCH; Causality; SPILLOVERS; CAUSALITY; VARIANCE